Harmoni dalam Keluarga: Konstruksi Hegemoni Patriarki Melalui Sastra Piwulang Pada masa Pemerintahan Pakubuwana IX - Nugroho, Yusro Edy; Lestari, Prembayun Miji; Fuadiyah, Ucik; Widodo, Widodo (Jayapangus Press, 2025)
“Harmony within the family” is a concept offered through sastra piwulang (didactic literature) during the reign of Pakubuwana IX at the Surakarta Palace. This concept underlies the construction of patriarchal hegemony embodied in several works of sastra piwulang, especially teachings intended for women at that time. This study focuses on analyzing sastra piwulang texts to understand how patriarchal ideology influenced social relationships and dynamics during that period, as well as how the concept of harmony was articulated through sastra piwulang. The results of the analysis show that almost all piwulang texts for women consistently carry the message of “family harmony,” which reinforces patriarchal domination in society and governance. This is reflected in the roles assigned to women, who were not entirely free to manage their existence and self-actualization. Concepts of power, control, and decision-making were held by men, resulting in gender inequality within the family. Amid this patriarchal domination, sastra piwulang functioned as a medium to articulate values that emphasized harmony within the family. The findings of this study can serve as a foundation for repositioning the role of women within Indonesian families, particularly Javanese families, in the development of gender equality programs in contemporary society.